Analisis SWOT Terhadap Tabungan IB Hijrah Haji Studi Kasus Bank Muamalat Kcp Stabat - Nurhasanah, Upik; Anggraini, Tuti (Universitas Batanghari Jambi, 2023)
The large costs that must be incurred to perform the Hajj pilgrimage are an obstacle for residents of Langkat. IB Hijrah Haji Savings is one of the savings that will simplify the process of traveling to Hajj. Who would have thought that there are still many people who don't know and don't know about Hajj savings, so the number of customers at Bank KCP Stabat is not needed. The problem formulation in this research was strengthened using SWOT analysis of IB Hijrah Haji Muamalat KCP Stabat Savings Bank. The original aim of this research was to find out how the number of IB Hijrah Haji Savings customers at Bank Muamalat KCP Stabat has developed and increased. The research method used in this research is theoretical and qualitative. Data collection uses interview methods and personal observation of the objects studied. The results of the SWOT matrix study show that Bank KCP Stabat loans have advantages consisting of good and quite fast service, free management fees, daily or monthly savings options and life premiums. The weakness of IB Hijrah Haji Savings is the lack of promotion due to inadequate human resources. The facilities offered by Hijrah Haji IB Savings are located in an environment that is generally dominated by Muslim residents so that it attracts the interest of other customers, as well as a strategic location that is easy to reach. The threat to the ib Hijrah Haji savings product is intense competition due to gaps between neighboring banks and crucial customer patterns when the same product is compared between banks..